Proceedings of International Conference on ICT for Sustainable Development ICT4SD 2015 Volume 1 - Satapathy, Suresh Chandra; Joshi, Amit.; Modi, Nilesh; Pathak, Nisarg; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
The two volumes of this book collect high-quality peer-reviewed research papers presented in the International Conference on ICT for Sustainable Development (ICT4SD 2015) held at Ahmedabad, India during 3 - 4 July 2015. The book discusses all areas of Information and Communication Technologies and its applications in field for engineering and management. The main focus of the volumes are on applications of ICT for Infrastructure, e-Governance, and contemporary technologies advancements on Data Mining, Security, Computer Graphics, etc. The objective of this International Conference is to provide an opportunity for the researchers, academicians, industry persons and students to interact and exchange ideas, experience and expertise in the current trend and strategies for Information and Communication Technologies.
Chapter 1. A Compact Triple and Quadruple Band Antenna for Bluetooth/WiMAX/WLAN/X-Band Applications -- Chapter 2. DDA: An Approach to Handle DDoS (Ping Flood) Attack -- Chapter 3. Approach to Accurate Circle Detection: Multithreaded Implementation of Modified Circular Hough Transform -- Chapter 4. Apache Hadoop Yarn MapReduce Job Classification Based on CPU Utilization and Performance Evaluation on Multi Cluster Heterogeneous Environment -- Chapter 5. Faster Load Flow Analysis -- Chapter 6. Fuzzy Link Based Analysis for Mining Informational Systems -- Chapter 7. Teaching-Learning-Based Optimization (TLBO) Approach to Truss Structure Subjected to Static and Dynamic Constraints -- Chapter 8. Enforcing Indexing Techniques in Berkeley DB Using Implementation of Hilbert Tree Algorithm -- Chapter 9. An Improvement in Performance of Optical Communication System using Linearly Chirped Apodized Fiber Bragg Grating -- Chapter 10. Enhancement of Minimum Spanning Tree -- Chapter 11. Feasibility Study of Proposed Architecture for Automatic Assessment of Use Case Diagram -- Chapter 12. Extraction of Web Content Based on Content Type -- Chapter 13. User Based Collaborative Filtering Using Bloom Filter with MapReduce -- Chapter 14. ICT Based Facilities Management Tools for Buildings -- Chapter 15. Study the Effect of Packet Drop Attack in AODV Routing and MANET and Detection of Such Node in MANET -- Chapter 16. UDP Flooding Attack Detection Using Information Metric Measure -- Chapter 17. Generalized MCDM Based Decision Support System for Personnel Prioritization -- Chapter 18. A Proactive Dynamic Rate Control Scheme for AIMD based Reactive TCP Variants -- Chapter 19. Investigating Varying Time Black Hole attack on QoS over MANET -- Chapter 20. Hybrid Approach to Reduce Time Complexity of String Matching Algorithm usingHashing with Chaining -- Chapter 21. INDTime: Temporal Tagger- First Step Towards Temporal Information Retrieval -- Chapter 22. A Secure Text Communication Scheme Based on Combination of Compression, Cryptography and Steganography -- Chapter 23. A Comparative Analysis of Feature Selection Methods and Associated Machine Learning Algorithms on Wisconsin Breast Cancer Dataset (WBCD) -- Chapter 24. ACE (Advanced Compression Encryption) Scheme for Image Authentication -- Chapter 25. An Efficient and Interactive Approach for Association Rules Generation by Integrating Ontology and Filtering Technique -- Chapter 26. Detection of Wormhole Attack in Wireless Sensor Networks -- Chapter 27. Comparative Analysis of MCML Compressor with and without Concept of Sleep Transistor -- Chapter 28. Design & Analysis of Ultra-Compact Four Band Wavelength Demultiplexer Based on 2D Photonic Crystal -- Chapter 29. Designing and Optimization of Nano-Ring Resonator Based Photonic Pressure Sensor -- Chapter 30. Classifying Nodes in Social Media Space -- Chapter 31. A Novel Hexagonal Shaped Based Band Stop Frequency Selective Surface with Multi-Band Applications -- Chapter 32. AXSM : An Automated Tool for XML Schema Matching -- Chapter 33. Development of Web Map Service For Open Street Maps (OSM) Data -- Chapter 34. Improved Indoor Positioning using RSS and Directional Antenna Integrating With RFID and Wireless Technology -- Chapter 35. Secured Cloud Data Storage - Prototype Trust Model for Public Cloud Storage -- Chapter 36. A Semi Circular Monopole Antenna for Ultra Wide Band Applications -- Chapter 37. Security Analysis of Different LFSR Based Ciphers to Propose a Novel Approach Compatible with Parallel Computing Platform, Providing Resistance Against Various LFSR Based Attacks -- Chapter 38. Microstrip Patch Antenna for IEEE 802.11a WLAN (5.25GHz) Application -- Chapter 39. Support Vector Machine Based Model for Host Overload Detection in Clouds -- Chapter 40. A Hybrid Face Recognition Scheme Using Contour and Gabor Wavelet -- Chapter 41. Data Dissemination Techniques and Publish/Subscribe Architecture in Vehicular Ad-hoc Networks -- Chapter 42. Data Acquisition with FPGA using Xilinx and LabVIEW -- Chapter 43. SRR and R-CSRR Loaded Reconfigurable Antenna with Multiband Notch Characteristics -- Chapter 44. Wireless Resonant Power Transmission -- Chapter 45. Fuzzy Clustering based Efficient Classification Model for large TCPdump data set using Hadoop framework -- Chapter 46. System-related Characteristic Based Leader Election Protocol for Cognitive Radio Networks -- Chapter 47. Passive Image Manipulation Detection using Wavelet Transform and Support Vector Machine Classifier -- Chapter 48. Intrusion Detection System with Snort in Cloud Computing -- Chapter 49. Rural E-Health Care Model -- Chapter 50. An Implementation Model for Privacy Aware Access Control in Web Services Environment -- Chapter 51. Comprehensive Review on Eye Close and Eye Open Activities Using EEG in Brain Computer Interface -- Chapter 52. Design of High Data Rate and Multipath Efficient Underwater Acoustic Communication System Using OFDM-DQPSK -- Chapter 53. A Hybrid Approach for Big Data Analysis of Cricket Fan Sentiments in Twitter -- Chapter 54. Performance Analysis of Medical Image Compression Techniques -- Chapter 55. Integrated Framework Using Frequent Pattern for Clustering Numeric and Nominal Data Sets -- Chapter 56. Image Encryption by Using Block Based Symmetric Transformation Algorithm (International Data Encryption Algorithm) -- Chapter 57. Content Based Watermarking Using MCA -- Chapter 58. Image Enhancement Based on Log-Gabor Filter for Noisy Fingerprint Image -- Chapter 59. Computational Performance Analysis of Ant Colony Optimization Algorithms for Travelling Sales Person Problem -- Chapter 60. Evaluating Performance of Reactive and Hybrid Routing Protocol in Mobile Ad-Hoc Network -- Chapter 61. Sentiment Based Data Mining Approach for Classification and Analysis -- Chapter 62. Offline Handwritten Sanskrit Simple and Compound Character Recognition Using Neural Network -- Chapter 63. Need of ICT for Sustainable Development of Power Sector -- Chapter 64. Development of Optical Impairment Minimization Technique for Radio Over Fiber Link -- Chapter 65. Mobile Waste Management for Smart Cities: Monitoring Sanitation through Living Labs -- Chapter 66. Optimized Implementation of Location Aware and Network Based Services for Power Efficient Android Applications -- Chapter 67. Power Consumption and Congestion Control of Rendezvous Node for Wireless Biosensor Network -- Chapter 68. Comparison of Different SimilarityFunctions on Hindi QA System -- Chapter 69. Preventing Faults: Fault Monitoring and Proactive Fault tolerance in Cloud Computing -- Chapter 70. Evolving the Reliability for Cloud System Using Priority Metric -- Chapter 71. Multilevel Priority Based Task Scheduling Algorithm for Workflows in Cloud Computing Environment -- Chapter 72. Efficient DNA Based Cryptographic Mechanism to Defend and Detect Blackhole Attack in MANETs -- <chapter 73. Sentiment Classification of Context Dependent Words -- Chapter 74. Opinion Mining Classification Based on Extension of Opinion Mining Phrases -- Chapter 75. Facial Expression Recognition Using variants of LBP and Classifier Fusion -- Chapter 76. FLSU Based Energy Efficient Protocol Design for WSN with Mobile Sink -- Chapter 77. Goal based Constraint Driven Dynamic RESTful Web Service Composition Using AI Techniques.
Keywords: Computational intelligence; Data mining; Computer-aided engineering; Telecommunication; Technological innovations; Computational Intelligence; Data Mining and Knowledge Discovery; Computer-Aided Engineering (CAD, CAE) and Design; Communications Engineering, Networks; Innovation and Technology Management